Pengaruh Biochar SP 50 yang di Modifikasi dan Plant Growth Promoting Rhizobacteria (PGPR) Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays saccharata Sturt) - Fachru Yuzairi U.S; Sumihar Hutapea; Ellen Lumisar Panggabean (Jurnal Ilmiah Pertanian ( JIPERTA), 2022)
This study aims to determine the response of growth and production of sweet corn plants to the application of modified SP-50 biochar and plant growth promoting rhizobacteria (PGPR). The design used was Factorial RAK which consisted of 2 treatment factors, namely: (1) Biochar SP-50 (B)     consisted of 3 levels, B0 = Without Biochar, B1 = Dose 10 tons/ha, B2 = dose 20 tons/ha. (2) PGPR (P) consists of 4 levels, treatment P0 = No PGPR, P1 = PGPR concentration of 1%, P2 = PGPR concentration of 2%, P3 = PGPR concentration of 3%. The results of this study showed that the application of Biochar SP-50 had a significant effect on stem diameter, number of leaves, weight of cobs with cocob per plot, weight of cobs without cob per plot, and a very significant effect on the number of seed rows. The best treatment is giving SP-50 biochar as much as 20 tons/ha. The provision of PGPR did not significantly affect the growth and production of sweet corn plants but gave a positive effect with the best concentrations of 1% and 3%. The combination of Biochar SP-50 and PGPR had a significant effect on plant height, cob weight with cob per sample and cob weight without cob per sample. The best treatment was giving Biochar SP-50 at a dose of 20 tons/ha and PGPR with a concentration of 3%.